2014
DOI: 10.1136/jnnp-2013-307110
|View full text |Cite
|
Sign up to set email alerts
|

Structural brain changes associated with depressive symptoms in the elderly with Alzheimer's disease

Abstract: Our findings suggest that depressive symptoms in AD patients are associated with cortical thinning in temporal and parietal regions. In addition, our findings suggest that τ protein pathology in these areas may contribute to the development of depressive symptoms in AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 44 publications
3
48
2
2
Order By: Relevance
“…These results likely explain the inconsistent results in previous FDG-PET studies regarding late-life depression where Aß status was not hitherto considered: Either hypermetabolism [11-13, 24] or hypometabolism [14-17] have been reported in late-life depressed subjects both in cognitively preserved, and impaired and AD patients. Moreover, PVEC was not applied in these FDG-PET studies investigating this topic, such that atrophy, as may occur in depressed subjects [37, 38], may have resulted in spurious findings of hypometabolism.…”
Section: Discussionmentioning
confidence: 99%
“…These results likely explain the inconsistent results in previous FDG-PET studies regarding late-life depression where Aß status was not hitherto considered: Either hypermetabolism [11-13, 24] or hypometabolism [14-17] have been reported in late-life depressed subjects both in cognitively preserved, and impaired and AD patients. Moreover, PVEC was not applied in these FDG-PET studies investigating this topic, such that atrophy, as may occur in depressed subjects [37, 38], may have resulted in spurious findings of hypometabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Impairment of hippocampal neurogenesis was accompanied by cognitive deficits in an animal model of AD; however, this impairment was not linked to depressive behavior in mice [38]. Indeed, alterations in limbic structures, including temporal and cortical regions, are common in patients with depression and AD [39]. A cohort study comparing neuroanatomical changes in patients with and without depressive symptoms in addition to AD revealed increased cortical thinning in AD patients with depressive symptoms compared with those without [39].…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…Indeed, alterations in limbic structures, including temporal and cortical regions, are common in patients with depression and AD [39]. A cohort study comparing neuroanatomical changes in patients with and without depressive symptoms in addition to AD revealed increased cortical thinning in AD patients with depressive symptoms compared with those without [39]. In addition, it was suggested that β amyloid pathology in the limbic structures contributed to the development of depressive symptoms in AD.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…Cortical amyloid and neurofibrillary tangle accumulation, which are believed to be the neuropathological markers of AD, were observed in late-life depression [56,57]. Neuropathological studies also suggested that AD patients with a history of depression or current depressive symptoms, even at the early stage of cognitive impairment, showed more severe AD pathology [58,59], and tau protein pathology in temporal and parietal regions may contribute to the development of depressive symptoms in AD [12]. In addition, WM lesions were proposed to interpret both depressive symptoms and cognitive impairment in elderly people [60] and have been found to be associated with depression in AD [61].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that depressive symptoms were associated with reduced gray matter (GM) volumes in the frontal and temporal cortices [8,9], and lower perfusion in the frontal and limbic gyri in patients with AD [10,11]. Lebedeva et al [12] examined the relationship of brain structure and cerebrospinal fluid biomarkers in AD patients with (dep-AD) and without depressive symptoms (nondep-AD), and found that dep-AD patients showed a greater negative correlation between total tau protein and cortical thickness in limbic gyri. However, little is known about the integrity of structural connectivity between these regions, termed as frontolimbic fiber tracts, in dep-AD patients.…”
Section: Introductionmentioning
confidence: 99%